Factors Affecting Production and Inefficiency of Smallholder Oil Palm Plantations in Riau Province: A Stochastic Frontier Analysis - Liana, Limetry; Siregar, Hermanto; Marulitua Sinaga, Bonar; Hakim, Dedi Budiman (Jurnal Agribisnis Indonesia, 2025)
This research, conducted in Siak Regency, a key area of smallholder plantations in Riau Province, holds significant implications for the local agricultural community. The main objective of this study is to analyze the factors that influence production and the inefficiency of smallholder oil palm plantations, analyzed using the Stochastic Frontier Analysis (SFA) method with STATA 17 software. Data were collected through field surveys and direct interviews with 132 smallholder farmers in Empang Pandan and Keranji Guguh Koto Gasib District Riau. The SFA estimation results show that five input variables significantly affect smallholder plantation production: land area, K fertilizer, organic fertilizer, and labour, which positively correlate with the increase in Fresh Fruit Bunch (FFB) production. In contrast, N fertilizer showed a negative correlation. We also found that the dummy variables for plantation management patterns and agricultural extension or training significantly impacted the inefficiency of smallholder oil palm plantations in Riau Province. The alternatives of the interaction between input variables on smallholder plantation production reveal that five alternative interactions between input variables significantly affect the increase in smallholder plantation production by more than 5 per cent, including the interaction of land area >< plant age, plant age >< pesticide, plant age >< labour, N fertilizer >< P fertilizer, and organic >< pesticide interaction.